2021
DOI: 10.1016/j.molstruc.2021.130897
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: In silico identification of potent α-ketoamide inhibitors targeting the main protease of the SARS-CoV-2

Abstract: The COVID-19 has been creating a global crisis, causing countless deaths and unbearable panic. Despite the progress made in the development of the vaccine, there is an urge need for the discovery of antivirals that may better work at different stages of SARS-CoV-2 reproduction. The main protease (M pro ) of the SARS-CoV-2 is a crucial therapeutic target due to its critical function in virus replication. The α-ketoamide derivatives represent an important class of inhibitors against the M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Despite significant progress in the development of MPIs, the binding mechanism and kinetic information about most inhibitors of the M pro have not been completely elucidated. [33][34][35][36][37] Therefore, understanding the molecular mechanism and conformational changes of inhibitor-M pro binding at the atomic level is critical for the development of highly effective MPIs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant progress in the development of MPIs, the binding mechanism and kinetic information about most inhibitors of the M pro have not been completely elucidated. [33][34][35][36][37] Therefore, understanding the molecular mechanism and conformational changes of inhibitor-M pro binding at the atomic level is critical for the development of highly effective MPIs.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 15 b (crystal structure of SARS-CoV-2 M PRO in complex with compound 12 , PDB code 6Y2F ), the X-ray experiment confirms the formation of the covalent adduct ( Figure 14 ): the α-ketoamide group enhances the interaction in the S1′ cleft thanks to the H bonds with His 41 , Gly 143 , Ser 144 , and Cys 145 , the S1 site accommodates the glutamine surrogate γ-lactam ring, the key fragment amidopyridone interacts with Glu 166 via two H bonds, and the tert -butyl moiety is inserted into the S2 pocket. 14 , 58 , 59 …”
Section: Electrophilic Warheads In Covalent Sars-cov-2 M Pr...mentioning
confidence: 99%
“…Analysis of the in silico data revealed that all three molecules interacted efficiently and stably with SARS-CoV-2 M PRO (similar to the reference compound 12 ) and also exhibited favorable pharmacokinetic and toxicological profiles. 59 …”
Section: Electrophilic Warheads In Covalent Sars-cov-2 M Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…as potent inhibitors against SARS-CoV-2 virus. [16][17][18][19][20][21][22][23][24][25][26][27] In the current epidemiological context, various molecular docking methodologies are progressing in several directions to develop novel medicines against SARS-CoV-2 virus, and the nature of the interaction between the crystal structure of copper complexes with a main protease of SARS-CoV-2 would be worthwhile studying. This work describes the structurebased design and synthesis of two novel square-planar trans-N 2 O 2 Cu(II) complexes [Cu(L 1 ) 2 ] (1) and [Cu(L 2 ) 2 ] (2) of 2-((Z)-(4methoxyphenylimino)methyl)-4,6-dichlorophenol (L 1 H) and 2-((Z)-(2,4-dibromophenylimino)methyl)-4-bromophenol (L 2 H) as potential inhibitors against the main proteases of the SARS-CoV-2 and HIV viruses.…”
Section: Introductionmentioning
confidence: 99%